(untitled) (KULT_online, 2015)
The comprehensive anthology Emotionen und Politik combines innovative and extensive research on questions regarding the appropriate and inappropriate politics of emotions, which are even more relevant in these politically turbulent times. The authors make a strong plea for engaging with emotions, and with emotionalization, in the political realm.